SCIENTIFIC SUBSTANTIATION OF THE POSITIVE AND NEGATIVE EFFECTS OF WATER BODIES ON ECOLOGY - Akramova Parvina Aminovna; G’afforova Dilshoda Ikromjon qizi (TADQIQOTLAR.UZ, 2024)
Abstract. This text delves into the scientific evidence supporting both the positive and negative impacts of water bodies on ecological systems. It likely explores how water bodies like lakes, rivers, and oceans can influence factors like biodiversity, climate regulation, and resource availability. The text might also discuss the potential negative effects of water bodies, such as habitat destruction, pollution dispersion, and the introduction of invasive species.